2014
DOI: 10.1071/an13076
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of LHβ and GnRHR genes and their association with the number of embryos recovered in goats

Abstract: The objective of the present study was to explore a predictor of superovulation response on the basis of associations between the number of embryos recovered and gene polymorphism. Variation in the goat LHβ and GnRHR genes was investigated using polymerase chain reaction–single-strand conformational polymorphism and DNA sequencing. Two single nucleotide polymorphisms (SNPs) were identified in the 5′-UTR of LHβ gene (A59C, P1 locus) and in the Exon 2 of GnRHR gene (T177A, P6 locus). At the P1 locus in both bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…The primers and genotyping identification method used in this study were suggested by Andreas et al [ 14 ] (GHR), [ 15 ] (GHRH), [ 16 ] (PIT1), and [ 17 ] (STAT5A). The polymerase chain reaction (PCR) analysis proceeded by admixing the DNA sample (5–50 ng/μl), primers (200 ng/μl), PCR Master Mix (Kapa Taq ReadyMix), and H 2 O (12 μl final volume).…”
Section: Methodsmentioning
confidence: 99%
“…The primers and genotyping identification method used in this study were suggested by Andreas et al [ 14 ] (GHR), [ 15 ] (GHRH), [ 16 ] (PIT1), and [ 17 ] (STAT5A). The polymerase chain reaction (PCR) analysis proceeded by admixing the DNA sample (5–50 ng/μl), primers (200 ng/μl), PCR Master Mix (Kapa Taq ReadyMix), and H 2 O (12 μl final volume).…”
Section: Methodsmentioning
confidence: 99%